Continuous Bioelectricity Generation from Phenol‐Contaminated Water by Mediator‐Less Microbial Fuel Cells: A Comparative Study between Air‐Cathode and Bio‐Cathode Systems. Issue 4 (4th July 2018) - Ziaedini, A.; Rashedi, H.; Alaie, E.; Zeinali, M.
Abstract: Due to metabolic activity of bacteria, microbial fuel cells (MFCs) can directly generate electricity by converting chemical energy of a biodegradable substrate to electrical energy. Simultaneous production of clean energy and wastewater treatment can be accomplished in these systems. In this study, phenol (100 ‐ 1, 000 ppm) as a toxic model of wastewater pollutant compounds was used as the sole source of carbon and energy for growth of bacteria and concomitant power generation in a dual‐chamber MFC. Experiments were conducted in two lab‐scale systems including an air‐cathode and a bio‐cathode MFC operating in continuous mode. Anode and bio‐cathode chambers were inoculated with aerobic activated sludge from an industrial wastewater treatment plant. The highest output power was obtained at a phenol concentration of 700 ppm in both air‐cathode (25 mW m −2 ) and bio‐cathode (5 mW m −2 ) MFCs without using any co‐substrate for the first time confirming the higher performance of the air‐cathode electrode in oxygen reduction reaction. Phenol removal efficiency for an influent concentration of 700 , ppm with an HRT of 125 min was 59.0% and 71.8% in bio‐cathode and air‐cathode MFCs, respectively. Cyclic voltammetry results confirmed involvement of both soluble and membrane‐bound mediator components in electrochemical activity of anodic biofilm.